Child Gender and Subjective Well-being of Older Parents in China - Lei Lei; Fengyu Wu; Yiming Xia (Global Labor Organization (GLO), 2023)
In many societies, parents prefer sons over daughters, but the well-being effects of child gender, especially in later life, are less studied. Using the latest two waves of the China Health and Retirement Longitudinal Study (CHARLS), this paper evaluates the impacts of having daughters on older parents' subjective well-being (SWB) in China, which has a rapidly aging population and the traditional preference for sons. Studying the cohort of parents whose child gender is as good as random, we find that having more daughters promotes older parents' SWB, especially overall life satisfaction, satisfaction with health, and satisfaction with children. Our results suggest that the increase in SWB is achieved through better health, more financial support from daughters, more spending on leisure and a lower probability of working. The positive SWB effects of daughters are found to be more salient among more vulnerable groups, including those who are older, less educated, and with fewer children.
Keywords: I31; J14; J16; 330; Subjective Well-being; Child Gender; Older Parents; China; Life Satisfaction; Domain Satisfaction